2013
DOI: 10.1111/ejn.12135
|View full text |Cite
|
Sign up to set email alerts
|

The brain's specialized systems for aesthetic and perceptual judgment

Abstract: We recorded brain activity when 21 subjects judged the beauty (aesthetic or affective judgment) and brightness (perceptual or cognitive judgment) of simultaneously presented paintings. Aesthetic judgments engaged medial and lateral subdivisions of the orbitofrontal cortex as well as subcortical stations associated with affective motor planning (globus pallidus, putamen-claustrum, amygdala, and cerebellar vermis), whereas the motor, premotor and supplementary motor areas, as well as the anterior insula and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 49 publications
8
99
0
1
Order By: Relevance
“…Although LO is a key region within the object recognition pathway, involved in many aspects of objects processing (for reviews, GrillSpector, 2003;Lacey & Sathian, 2011), such as extracting shape information from both two-and three-dimensional objects (Kourtzi & Kanwisher, 2000;Malach et al, 1995), object size judgments (Eger, Ashburner, Haynes, Dolan, & Rees, 2008;Pourtois, Schwarts, Spiridon, Martuzzi, & Vuilleumier, 2009), and even semantic aspects (i.e., object categorization and naming) (Eger et al, 2008), its functions may go beyond mere shape detection and object recognition. Specifically, LO is one of the brain regions whose activity has been related to aesthetic experience of visual art in neuroimaging studies (Cupchik et al, 2009;Ishizu & Zeki, 2013;Vartanian & Goel, 2004). Importantly for our study, found that activity in right LO correlated positively with aesthetic evaluation of artistic images.…”
Section: Introductionsupporting
confidence: 63%
“…Although LO is a key region within the object recognition pathway, involved in many aspects of objects processing (for reviews, GrillSpector, 2003;Lacey & Sathian, 2011), such as extracting shape information from both two-and three-dimensional objects (Kourtzi & Kanwisher, 2000;Malach et al, 1995), object size judgments (Eger, Ashburner, Haynes, Dolan, & Rees, 2008;Pourtois, Schwarts, Spiridon, Martuzzi, & Vuilleumier, 2009), and even semantic aspects (i.e., object categorization and naming) (Eger et al, 2008), its functions may go beyond mere shape detection and object recognition. Specifically, LO is one of the brain regions whose activity has been related to aesthetic experience of visual art in neuroimaging studies (Cupchik et al, 2009;Ishizu & Zeki, 2013;Vartanian & Goel, 2004). Importantly for our study, found that activity in right LO correlated positively with aesthetic evaluation of artistic images.…”
Section: Introductionsupporting
confidence: 63%
“…Indeed, previous findings in the neuroaesthetics literature have suggested that vmPFC is generally involved in aesthetic evaluations (Ishizu and Zeki 2013; Brown et al 2011). For example, Ishizu and Zeki (2011) found overlapping response in vmPFC for beautiful paintings and music, demonstrating that a common evaluative mechanism in vmPFC is recruited by stimuli of different modalities (visual, auditory).…”
Section: Discussionmentioning
confidence: 95%
“…The OFC is a key component of the traditional reward circuitry, implicated in the representation of reward value (Kringelbach & Radcliffe, 2005). Activation in the OFC has been observed during aesthetic judgements (Ishizu & Zeki, 2013;Jacobsen, Schubotz, Höfel, & Cramon, 2006) and the experience of beauty across different sensory modalities (Ishizu & Zeki, 2011), suggesting a potential role for this region in the aesthetic assessment of faces, including judgements of facial attractiveness. In light of research demonstrating activation in brain regions associated with the processing of rewards (e.g., the OFC, prefrontal cortex or PFC 1 , nucleus accumbens or NAcc), Senior (2003) proposed an extension of Haxby's model incorporating specific involvement of the reward-system for the processing of facial appearance, especially relevant for the perception of facial attractiveness (Figure 1).…”
mentioning
confidence: 99%